An assessment of Archives and Record Assortment in selected University Libraries of Bangladesh: a Study - Hossain, Md. Anwar; Barooah, P. K. (Access: An International Journal of Nepal Library Association, 2023)
It was intended to analyze and assess the current state of archives and records management in some selected university libraries of Bangladesh as well as to evaluate present status of implementation of IR in these selected libraries. To draw inferences and make recommendations, a survey was conducted in selected public and private university libraries of Bangladesh. The universities were selected for this study on the basis of their position within 10th in the 2020 Uni Rank list published in Bangladesh. The primary data were collected through questionnaire, interview and observation methods and secondary data were derived from literature search. The findings of the study show that 50% public university library use digital repository as archives whereas 90% private university libraries preserve the archives digitally as well as manually. The study also reveals that maximum (90%) private university libraries use archival repository though the number of repositories are increasing slowly. On the other hand, 50% public university libraries use the repository but the number of manual collection of these university library are much higher than others libraries. The study also clearly indicates that public libraries are ahead of private university libraries in preserving the number of manual collection. The findings of the study show that fifty percent public university libraries use digital repository as archives whereas near almost all private university libraries preserve the archives digitally along with manual system. The study revealed that the difference between manual collection of public and private university libraries was significant(p=0.0384), on contrast, the difference between public and private university library collection regarding IR collection is not significant (p=0.9937). The study clearly indicates that public libraries are ahead of private university libraries in preserving the number of manual collection whereas private university is ahead of public university in the implementation of IR system and its collections.